Sinergi Kepemimpinan Demokratis dan Transaksional Meningkatkan Dinamika Industri Fashion Muslim di Indonesia: Studi KEKE Busana - Bunga Ayu Ratnasari; Pratami Wulan Tresna; Bambang Hermanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The influence of Muslim fashion is increasing with the rise of social media, making it a trend that many people now follow. The Muslim fashion industry in Indonesia, such as Keke Busana, is experiencing rapid development but also faces challenges in adapting to changes in consumer demand. This research aims to examine the importance of combining two leadership styles in fashion companies and to explore the most appropriate leadership style in the Muslim fashion industry. The research method used was qualitative, involving in-depth interviews with the Chief Executive Officer (CEO) of Keke Busana. The research results show that combining democratic and transactional leadership styles can gradually improve company performance. Leaders of Muslim fashion companies are advised to consider innovation in leadership models to avoid hierarchical organizational structures that can limit flexibility and creativity.